2013
DOI: 10.1111/acer.12307
|View full text |Cite
|
Sign up to set email alerts
|

Modest Long‐Term Ethanol Consumption Affects Expression of Neurotransmitter Receptor Genes in the Rat Nucleus Accumbens

Abstract: Background: Over 100 million people worldwide are affected by alcohol use disorders. These conditions usually take years to develop where an initial, voluntary consumption is gradually replaced by a compulsive intake of alcohol. The exact mechanisms behind this transition remain unknown. However, ethanol (EtOH) is known to interact with several neurotransmitters and receptors in the central nervous system, and chronic EtOH consumption causes alterations in these neurotransmitter systems, proposed to contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…It is also possible that if we had assessed palatability using a taste reactivity test, rather than lickometer analysis we would have found a different result. Changes in MOR levels in the NAc due to alcohol exposure may account for the lack of altered palatability or other effects reported here: mu-opioid receptor gene expression is reported to increase after 2 and 4 months of moderate alcohol pre-exposure (similar to the levels seen here) (Jonsson et al, 2014), though decreases in MOR expression (Saland et al, 2005) or no change (Shah et al, 1997) have been reported with other sets of exposure parameters. Finally, DAMGO’s lack of effect on palatability-related measures of alcohol consumption may be related in part to the taste of alcohol functioning as a conditioned reinforcer, rather than as a primary reinforcer, or to its mixed hedonic and aversive taste qualities (Bice et al, 1992).…”
Section: Discussionsupporting
confidence: 65%
“…It is also possible that if we had assessed palatability using a taste reactivity test, rather than lickometer analysis we would have found a different result. Changes in MOR levels in the NAc due to alcohol exposure may account for the lack of altered palatability or other effects reported here: mu-opioid receptor gene expression is reported to increase after 2 and 4 months of moderate alcohol pre-exposure (similar to the levels seen here) (Jonsson et al, 2014), though decreases in MOR expression (Saland et al, 2005) or no change (Shah et al, 1997) have been reported with other sets of exposure parameters. Finally, DAMGO’s lack of effect on palatability-related measures of alcohol consumption may be related in part to the taste of alcohol functioning as a conditioned reinforcer, rather than as a primary reinforcer, or to its mixed hedonic and aversive taste qualities (Bice et al, 1992).…”
Section: Discussionsupporting
confidence: 65%
“…The lack of strong transcriptomic alterations in NAc is in line with other related studies in the same region [10, 24, 25], which is somewhat surprising since the NAc repeatedly is considered as one of the main regions involved in addictions, including alcoholism [26, 27]. This is indicative of region and temporal dependent molecular changes that might lead to addiction [9, 28], since numerous alterations have been found in other areas such as the prefrontal cortex and amygdala [1012, 29]. …”
Section: Discussionsupporting
confidence: 80%
“…A total of 22 male outbred Wistar rats (Taconic, Ejby, Denmark), weighing 160-180g at the start of experiments were single housed during eight weeks, a time period previously reported to be sufficient for the detection of potential alcohol-induced alterations in gene expression [9]. Animals were housed with a regular 12h light cycle and had ad lib access to tap water and rodent chow (Lantmännen, Stockholm, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dopamine deficiency hypothesis is supported by a study showing decreased dopamine receptor gene expression after several months of voluntary alcohol drinking [103]. In addition, microdialysis studies in freely moving outbred rats show a decreased dopamine output in the NAc, compared to age-matched alcohol-naïve controls, following 7 weeks [104] and 10 months [29] of voluntary alcohol consumption.…”
Section: Preclinical Evidence: Chronic Alcohol Exposure and Dopaminementioning
confidence: 95%